Fatty acid composition of Aconitum orientale miller and A-nasutum Fisch ex Reichb seeds, a chemotaxonomic approach - Bagci, E; Özqelik, H (Kluwer Academic/Plenum Publ, 2002)
[Abstract Not Available]
3rd IUPAC International Conference on Biodiversity -- NOV 03-08, 2001 -- ANTALYA, TURKEY
Keywords: Diterpenoid Alkaloids